Islamic Republic of Afghanistan : Request for an Extension of the Three-Year Arrangement Under the Extended Credit Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The arrangement, for SDR 81 million (50 percent of quota), was approved on June 26, 2006. The Executive Board extended the arrangement until March 31, 2010, and rephased remaining disbursements to allow for a review. The authorities intend to frame the new homegrown program within a wider development agenda that they will announce at a donor conference in Kabul on July 20. The revenue target was exceeded by a large margin, yielding an increase in the tax-to-GDP ratio from 6.9 percent in 2008/09 to 8.9 percent in 2009/10.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet